Morphological and molecular assessment of muscle metacercariae infecting tench Tinca tinca from fish farms and wild populations in Germany - Claudina Mata-Marcano; Matthias Stöck; Klaus Knopf (Scientific Reports)
Abstract Fish can be infected with metacercariae (the final larval stage) of different species of potentially zoonotic digenetic trematodes (flukes). The fish-borne zoonotic trematodes thus compromise food safety and present a major threat for human health. Reducing the risk of human infections requires careful assessment and accurate taxonomic identification of these parasites. Here, we analysed metacercariae in muscle tissue of tench (Tinca tinca), sampled between March and September 2022 from three fish farms and three natural waterbodies in Germany. Whenever possible, we combined morphological and molecular data from the very same individual metacercariae using mitochondrial cytochrome oxidase c subunit 1 (cox1) and nuclear internal transcribed spacer 1 (ITS1) for species identification. Three morphotypes of metacercariae were found in the muscle of tench, corresponding to the trematode species Pseudamphistomum truncatum Rudolphi, 1819 (Opisthorchiidae), Hysteromorpha triloba Rudolphi, 1819 (Diplostomidae), and Paracoenogonimus ovatus Katsurada, 1914 (Cyathocotylidae). The high prevalence of metacercariae of P. truncatum and P. ovatus, both with zoonotic potential, poses a risk for human infections if undercooked or raw tench is consumed.